A ventilation technique for oxygenation and carbon dioxide elimination in CPR: Continuous insufflation of oxygen at three levels of pressure in a pig model. (December 2015) - Ordelman, Simone C.M.A.; Aelen, Paul; Woerlee, Pierre H.; van Berkom, Paul F.J.; Scheffer, Gert-Jan; Noordergraaf, Gerrit J.
Abstract: Aim: Pulmonary ventilation remains an important part of cardiopulmonary resuscitation, affecting gas exchange and haemodynamics. We designed and studied an improved method of ventilation for CPR, constructed specifically to support both gas exchange and haemodynamics. This method uses continuous insufflation of oxygen at three levels of pressure, resulting in tri-level pressure ventilation (TLPV). We hypothesized that TLPV improves gas exchange and haemodynamics compared to manual gold standard ventilation (GSV). Methods: In 14 pigs, ventricular fibrillation was induced and automated CPR performed for 10 min with either TLPV or GSV. After defibrillation, CPR was repeated with the other ventilation method. Gas exchange and haemodynamics were monitored. Data are presented as mean ± standard error of the mean. Results: TLPV was superior to GSV for PaO2 (163 ± 36 mmHg difference; P  = 0.001), and peak AWP (−20 ± 2 cmH2 O difference; P  = 0.000) and higher for mean AWP (8 ± 0.2 cmH2 O difference; P  = 0.000). TLPV was comparable to GSV for CPP (5 ± 3 mmHg difference; P  = 0.012), VCO2 (0.07 ± 0.3 mL/min/kg difference; P  = 0.001), SvO2 (4 ± 3%-point; P  = 0.001), mean carotid flow (−0.5 ± 4 mL/min difference; P  = 0.016), and pHa (0.00 ± 0.03 difference; P  = 0.002). The PaCO2 data do not provide a conclusive result (4 ± 4 mmHg difference). Conclusion: We conclude that the ventilation strategy with a tri-level pressure cycle performs comparable to an expert, manual ventilator in an automated-CPR swine model.